Analysis of risk factors of cord blood transplantation for children. Issue 12 (26th August 2013) - Goldstein, Gal; Bielorai, Bella; Stein, Jerry; Stepensky, Polina; Elhasid, Ronit; Zaidman, Irena; Chetrit, Angela; Yaniv, Isaac; Nagler, Arnon; Toren, Amos
Abstract Background As cord blood (CB) is being used frequently as a source for heamtopoetic stem cell transplantation defining risk factors for transplantation outcome is an important issue. Procedure The data of all single unit CB transplantation preformed in Israel from 1992 to 2011 were collected. The risk factors for myeloid engraftment, event free survival (EFS) and overall survival (OS) were studied in 87 children. Results There were 49 children with hematological malignancies and 38 with non‐malignant diseases. Cumulative rate of neutrophil recovery was 78.3%, while median time to myeloid recovery was 26 days. The incidence of platelet engraftment at 150 days was 53%, and the median time to platelet recovery was 36 days. ABO blood group matching between CB unit and recipient was associated with superior myeloid engraftment. Acute graft versus host disease of grades II–IV occurred in 33% of the patients. Chronic graft versus host disease occurred in 16% of patients. Probabilities of EFS and OS at 1 year were 45% and 57%, respectively. Factors associated with inferior OS were Rh major mismatch versus matched Rh and transplantation from unrelated donor versus related donor. Conclusions These results indicate that matching of ABO blood groups is an important factor that affects engraftment, and also that Rh matching seem to have an impact on OS, which was not previously described in the setting of CB transplantation. Pediatr Blood Cancer 2013;60:2007–2011. © 2013 Wiley Periodicals, Inc.